BUDAYA ORGANISASI MAPALUS DALAM AKTIVITAS SOSIAL MASYARAKAT DI DESA RANOLAMBOT KECAMATAN KAWANGKOAN BARAT KABUPATEN MINAHASA - ONSU, AMELIA VONNI; RURU, JOORIE; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2020)
This study aims to find out how the culture of mapalus organizations in the social activities ofRanolambot village, Kawangkoan Barat District, Minahasa Regency. The study used a descriptivequalitative analysis design. Data collection techniques used were observation, interviews, documentation.To see how the culture of mapalus organizations in community social activities in the village ofRanolambot. Researchers used 4 indicators, namely: family, consensus agreement, cooperation, unity andunity. Based on the results of this study stated that the mapalus organizational culture in the village ofRanolambot has begun to disappear where there are still people who look ignorant in their participation incommunity service.Thus it can be concluded that mapalus organizational culture in community socialactivities in the village of Ranolambot is still not good.Keywords: Organizational culture, mapalus, community social activities.